Seeking ways in improving promotion and provision of emergency contraception in Addis Ababa Hospitals - Kassaye, Teshome; Dwivedi, A.D. (Ethiopian Journal of Reproductive Health, 2018)
Abstract Objective: To assess attitudes of physicians working in Addis Ababa government hospitals towards routine counseling and advance prescription of emergency contraception (EC). Methods: A cross sectional descriptive study on attitudes of physicians towards routine counseling and advance prescription of EC was performed on 445 physicians working in Addis Ababa public hospitals. A standardized questionnaire which assessed knowledge, attitudes and practices (KAP) on EC provision and routine counseling and advance prescription of EC were administered among participants. Results: Out of the total 445 physicians, there was an overall response rate of 86.1%. Only 55.3% participants received a very good and good knowledge score. Physicians of gynecological and obstetrics department were more knowledgeable than others (p< .0001.). Attitudes of physicians were favorable (64%) towards EC. Being a member of gynecological and obstetrics department showed a very good knowledge score, and past counseling and prescribing EC had favorable attitudes. The majority 72.4% (240) have never prescribed EC. Physicians who ever counseled and prescribed EC before the survey were more likely to have a very good knowledge score (181 p < 0.0001), favorable attitudes (176 p< .001) and past prescribing (124 p < 0.15) than others. The majority of the respondents 316 (83.6%) agreed on the role of routine counseling and advance prescription supply of EC, in provision, promotion and information dissemination, and among them 68.8%, were willing to prescribe EC in the future. More than 90% had some concerns like it might encourage repeated use. Eighty four percent mentioned mass media, printed materials, women organization and telephone including text messages and involvement of male partners as better options for EC advocacy, information dissemination, and provision. Conclusion: Attitudes of physicians on EC was favorable but knowledge and practices of EC were very low. Strategy to increase its access through routine counseling and advance prescription supply to all women is taken not only positively but also majority of them are willing to offer EC in advance by prescription and addressed the need of information on EC for providers and clients. Improving KAP on EC is crucial and physicians need to be provided with accurate and up to date information through comprehensive training and updates on EC. Keywords: Emergency contraception, KAP, physicians, contraception.